Revealing the Endophyte Potentials to Improve Sugarcane Health and Support an Increase in Sugar Production - TITIEK YULIANTI (Puslitbang Perkebunan, 2012)
Escalation of sugarcane productivity to support self-sufficiency in sugar in 2014 should be followed with improving environmentally friendly cultivation sys-tem. One of the alternatives is the use of endophyte. Endophyte is a microorganism naturally integrated with healthty plant and lives inside plant tissues without giving any negative effects. Endophyte could act as plant growth promotor, increase yield through phytohormone production and nutrition supplyer, and as soil contaminant neutralizer so it increases phyto-remediation and plant resistance against abiotic stress, and acts as biocontrol agent for pests and diseases. Even through biotechnology evolution, endophyte is used to produce antibiotic for medicine or pharmacy, biomass, biofuel, and media for transgenic resistance to insect pest or pathogen. Bacterial endohyte Acetobacter diazotrophicus (Syn. : Gluconacetobacter diazotrophicus) provides 60-80% of Nitrogen required by sugarcane through N2 fixation from air, so it suits as source of biofertilizer. In addition, there are many endophytes found as root or plant growth promotor and as biocontrol agent for pathogen. In Indonesia, research on the role of endophyte on sugarcane is still limited, hence it needs to reveal and determine the potential of endophyte to improve sugarcane health as wel as supporting acceleration of increasing sugar production. Keyword: endophyte, sugarcane, environment, pathogen, nutrition